A QUALITATIVE STUDY OF TRANSGENDER CHILDREN WITH EARLY SOCIAL TRANSITION: PARENT PERSPECTIVES AND CLINICAL IMPLICATIONS - Wong, Wallace; Drake, S (PEOPLE: International Journal of Social Sciences, 2017)
Social transition for young children is a field fraught with conflicting perspectives and limited research. This paper examines experiences of families allowing social transition for young children from the parent’s perspectives and introduces practical ideas from our clinical experiences. Participants were parents of children ages 4 to 9 with gender dysphoria (n=15) in British Columbia, Canada. The children ranged in gender identity and had been under the care of the gender health clinic for a period of one to four years. Participants were self-referred the study and participated in a focus group to describe experiences allowing social transition. Results were transcribed and analyzed using constant comparison qualitative method. Five major themes emerge from this study, including positive changes in the relationship between the child and the parent/family, improvement in social relationship, parent flexibility in the relationship between the child and the parent/family, improvement in social relationship, parent flexibility and preparation for change, and expansion of different gender roles and expressions. Findings indicate social transition for young children results in positive changes in the mood of the child and the child-caregiver relationship as well as improvement in general social relationships. Different clinical implications of permitting early social transition on social development are discussed.